Policy instruments matter: Support schemes for renewable energy capacity in worldwide comparison. (September 2022) - Barnea, Gil; Hagemann, Christian; Wurster, Stefan
Abstract: Renewable energy is a key component for increasing resilience and limiting climate change, along with ecological benefits and energy independence for developed and less developed countries alike. Surprisingly, the expansion of wind and solar energy capacity varies tremendously between countries, even considering the different economic and natural conditions. While some countries have changed their energy mix to a substantial extent, others have not yet unlocked their potential for renewable energies. Our paper thus asks for diverse factors explaining varying patterns of renewable energy potential exploitation from 2010 to 2019. Besides structural conditions and general political factors, we focus on specific regulatory, market, and funding policy instruments packages. We find that while regulatory and market instruments, as well as electoral democracy and government effectiveness matter for the expansion of wind and solar electricity production, high oil rents seem to counteract it. While regulatory instruments played a crucial role in the 'implantation phase' at the beginning of the 2010s, its impact declined over time while market instruments' effect increased over the 'sprouting phase' years of 2010s. This points to an increased market-readiness of the technology following years of market penetration. Highlights: State capacities and electoral democracy support the expansion of renewables. Regulatory instruments helped renewables in the early years to take off. Market instruments took precedence in the later 2010s reflecting decreasing prices. Government effectiveness with matching policies matters for renewables expansion. GDP per capita seems to play no significant role in expanding solar and wind energy.